Tentative identification of 20(S)-protopanaxadiol metabolites in human plasma and urine using ultra-performance liquid chromatography coupled with triple quadrupole time-of-flight mass spectrometry - Ling, Jin (J Ginseng Res, 2019)
BACKGROUND: 20(S)-Protopanaxadiol (PPD), the aglycone part of 20(S)-protopanaxadiol ginsenosides, possesses antidepressant activity among many other pharmacological activities. It is currently undergoing clinical trial in China as an antidepressant. METHODS: In this study, an ultra-performance liquid chromatography coupled with triple quadrupole time-of-flight mass tandem mass spectrometry method was established to identify the metabolites of PPD in human plasma and urine following oral administration in phase IIa clinical trial. RESULTS: A total of 40 metabolites in human plasma and urine were identified using this method. Four metabolites identified were isolated from rat feces, and two of them were analyzed by NMR to elucidate the exact structures. The structures of isolated compounds were confirmed as (20S,24S)-epoxydammarane-12,23,25-triol-3-one and (20S,24S)-epoxydammarane-3,12,23,25-tetrol. Both compounds were found as metabolites in human for the first time. Upon comparing our findings with the findings of the in vitro study of PPD metabolism in human liver microsomes and human hepatocytes, metabolites with m/z 475.3783 and phase II metabolites were not found in our study whereas metabolites with m/z 505.3530, 523.3641, and 525.3788 were exclusively detected in our experiments. CONCLUSION: The metabolites identified using ultra-performance liquid chromatography coupled with triple quadrupole time-of-flight mass spectrometry in our study were mostly hydroxylated metabolites. This indicated that PPD was metabolized in human body mainly through phase I hepatic metabolism. The main metabolites are in 20,24-oxide form with multiple hydroxylation sites. Finally, the metabolic pathways of PPD in vivo (human) were proposed based on structural analysis.